A study of menstrual hygiene among rural adolescent school girls in rural field practice area of a medical college, Davangere- a cross sectional study - Basavaraju, Vidya; Bukanakere, Chetan Lakshmikantha; Dsouza, Madonna J.; Mallenahalli, Ashok Kumar Shivakumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Adolescence in girls signifies the transition from girlhood to womanhood; one fifth of world population is between 10 and 19 years old. Menstruation is a phenomenon unique to the females. Menstruation is a monthly occurrence that requires access to appropriate materials and facilities, without which, females suffer from poor menstrual hygiene which restricts their movement and self-confidence. Increased knowledge about menstruation right from childhood may escalate safe practices and may help in mitigating the suffering of millions of women. Methods: A cross sectional study was conducted among 200 adolescent girls in a rural field practice area of S. S. Institute of Medical Sciences. Data on socio-economic variables and menstrual characteristics were collected using pre-tested questionnaires for a period of two months from September to October 2018. Results: Total of 200 girls was interviewed. 87.6% of the girls were aware about menstruation prior to the attainment of menarche. Mothers were the first informants in about 56.5% girls. Overall 51.5% adolescent girls were using sanitary napkins as menstrual absorbent, while 45.6% were using used cloths. 97.6% girls practiced different restrictions during menstruation. Some of the sociodemographic factors like religion, type of family and mother’s education, SES were significantly associated with menstrual hygienic practices. Conclusions: There is a need to educate the girls about menstruation, its importance and hygiene maintenance; to enable them to lead a healthy reproductive life in future.